The conditions of sustainable food security : an integrated conceptual framework - Duhaime, Gérard; Godmaire, Anne (GÉTIC, Université Laval, 2024)
Based upon a review of the world literature, this chapter presents an integrated conceptual framework of the conditions of food security. The systemic model provides definitions of the principal variables, as well as explanations and illustrations of their mutual - and most of the time multidimensional - relationships. The fundamental framework is that food security and food insecurity (both being potentially sustainable or not) is the result of the relations between social factors (demography, health), intermediating mechanism (food production and circulation in the market and the non-market spheres), and food consumption determinants (accessibility, availability). The framework is drawn here in order to provide the readers with a tool to situate each of the following chapters into a global context, to provide the analytical tool that will guide the synthesis of this book which is presented in the last chapter.